Creating worldwide community safety with present technology and privacy protection: The e-JIKEI Network project - Kobayashi, Kohjiro; Maru, Koichi; Ohta, Naoya; Yoshiura, Noriaki; Ueda, Hiroshi; Yupapin, Preecha; Fujii, Yusaku (My University, 2010)
In this paper, the e-JIKEI Network project, a project for creating community safety with present day technology, is reviewed. With the e-JIKEI Network, each individual watches around his/her house using cameras as his/her eyes, a computer as his/her brain, and software. For privacy protection, we propose the e-JIKEI with Privacy Protection, in which people who own and manage images (the owner) and people who have the right to view the images (the viewer) are separated by the encryption of the images. In order to evaluate our concept, social experiments have been performed. The present status and future prospects have been discussed in detail.
Keywords: Altruism; Community safety; Crime prevention; Criminal identification; e-JIKEI Network; Internet; network camera; Present technology; Privacy protection; Security